The implementation of literary works In teaching literary translation - Sylvie Meiliana (STAI Miftahul Ula Nganjuk, 2020)
The aim of this research is to show the implementation of literary works in literary translation by giving the way how to implement the literary work in revealing cultural terms found in a literary work, namely Achmad Tohari’s Ronggeng Dukuh Paruk Novel. Based on the literary work, the research on literary translation is done by investigating the translation procedure applied in translating the cultural terms from Indonesian into English. This research used a descriptive qualitative method with content analysis technique done by taking the flow model followed by data reduction, data presentation, and conclusion. The analysis used a semantic approach and Peter Newmark’s translation procedures. Result of the research shown by implementing literary work, the research of literary translation reveals that there are 16 cultural terms and classified in 6 different categories, they are musical instruments, clothes, accessories, work and leisure, activities and procedures, and religious terms. In translating the novel, there are 7 translation procedures used by the translator, they are transference, naturalization, cultural equivalent, functional equivalent, descriptive equivalent, couplets, and notes.